The effectiveness of two smoking cessation programmes for use in general practice: a randomised clinical trial. Issue 6741 (30th June 1990) - Slama, K; Redman, S; Perkins, J; Reid, A L; Sanson-Fisher, R W
Abstract : OBJECTIVE–To evaluate a structured, behavioural change, smoking cessation intervention designed for use within general practice. DESIGN–Randomised controlled clinical trial. SETTING–General practices in Newcastle, Australia. PATIENTS–311 Patients identified as smokers by a screening question were enrolled in the study. Of these, 101 were assigned to a structured behavioural change programme, 104 to a simple advice programme adapted from previous research, and 106 to a control group. No significant differences were found between groups for demographic and smoking related variables before the study. INTERVENTIONS–Patients in the simple advice group received a brief statement of advice from the general practitioner as well as three pamphlets; those in the structured intervention group were given strategies which included attitude and behavioural change programmes as well as techniques to aid compliance. The amount of smoking in all groups was assessed by self reports with validation by measurement of salivary cotinine concentrations. MAIN OUTCOME MEASURE–Significant increase in cessation rates. CONCLUSIONS–Significant differences between controls and the structured behavioural change group were found at the one month follow up, but only for self reported abstinence. The simple advice programme did not produce any significant differences over the control group. General practitioner evaluation of the structured programme highlighted difficulties in relation to the duration of the intervention. Overall the structured programme in its present form did not appear to be an effective programme for use within general practice.